Nilai-Nilai Pendidikan Pembelajaran Matematika dari Perspektif Islam: Telaah Materi Pembelajaran Operasi Bilangan Bulat - Firdaus Firdaus; Hasanah Ritonga (UIR Press, 2022)
The effects of promiscuity today cause the younger generation to be damaged. In addition, it also causes the character values or morals that exist in children to begin to erode slowly. Teachers can build religious characters for students through the integration of educational values into mathematics learning in order to form Islamic human beings. Students need religious character to deal with changing times and moral decline. not only through religious education, but also through Islamic mathematics instruction, particularly in integer operationsThis study aims to determine the character values in learning integer operations. This type of research is library research with a qualitative approach, while to analyze it the researcher uses content analysis or content analysis. The results of the data analysis carried out contained six character values in the integer operation material, namely the value of discipline, the value of helping, the value of conscientiousness, the value of hard work, the value of religion, and the value of honesty. With the application of Islamic values, character or morality is formed in students.